Human dignity - Kateb, George (Cambridge, Mass. : Belknap Press of Harvard University Press, 2011)
We often speak of the dignity owed to a person. And dignity is a word that regularly appears in political speeches. Charters are promulgated in its name, and appeals to it are made when people all over the world struggle to achieve their rights. But what exactly is dignity? When one person physically assaults another, we feel the wrong demands immediate condemnation and legal sanction. Whereas when one person humiliates or thoughtlessly makes use of another, we recognize the wrong and hope for a remedy, but the social response is less clear. The injury itself may be hard to quantify. Given our concern with human dignity, it is odd that it has received comparatively little scrutiny. Here, George Kateb asks what human dignity is and why it matters for the claim to rights. He proposes that dignity is an "existential" value that pertains to the identity of a person as a human being. To injure or even to try to efface someone's dignity is to treat that person as not human or less than human--as a thing or instrument or subhuman creature. Kateb does not limit the notion of dignity to individuals but extends it to the human species. The dignity of the human species rests on our uniqueness among all other species
The idea of human dignity -- Individual status and human rights -- Human uniqueness : traits and attributes -- Human stature and great achievements
Includes bibliographical references (pages 219-226) and index
Keywords: Human rights; Dignity